ORIENTAL RESTAURANTS AND THEIR STRATEGIES ON THEIR MARKETING CHANNELS - Negreti, Amanda dos Santos; Pigatto, Gessuir [UNESP]; Camargo Ferraz Machado, Joao Guilherme de [UNESP] (Univ Comunitaria Regional Chapeco-unochapeco, 2020)
Given the growing consumer preference for eastern food and the increase in restaurants offering this cuisine, the aim of this article was to characterize and analyze the form of selection of distribution and communication channels used by restaurants offering oriental food. As a method, we used the exploratory research and multisite studies, the data collection was done through direct observation, documentary analysis and focused interview, with the use of a form applied to the managers of six establishments located in the Northwest of Sao Paul. The results showed that the distribution channels used by these establishments vary between traditional and alternative (delivery and food trucks). It is concluded that managers use competitive strategies in the management of the distribution channels and communication of their establishments, with emphasis on the location, use of the environment and communication tools, according to the channel used, especially the use of social networks and mobile applications (APP) across all companies by offering services according to changes in consumer behavior. Also, it was possible to verify that the strategic decisions of the managers of the respective establishments are consistent with the distribution channels used.
Keywords: Distribution channels; Food services; Strategy